The Pictorial Fit-Frail Scale Malay Version (PFFS-M): Predictive Validity Testing in Malaysian Primary Care - Sally Suriani, Ahip; Olga, Theou; Shazlina, Shariff-Ghazali; Azah, Abdul Samad; Sabrina, Lukas; Ummu Kalsum, Mustapha; Renuka, Visvanathan (Serdi Publisher, 2023)
The purpose of this study was to evaluate the association between Pictorial Fit Frail Scale-Malay version (PFFS-M) and adverse outcomes,such as falls, new disability, hospitalisation, nursing home placement,and/or mortality, in patients aged 60 and older attending Malaysian public primary care clinics. We assessed the baseline PFFS-M levels of 197 patients contactable by phone at 18 months to determine the presence of adverse outcomes. 26 patients (13.2%) reported at least one adverse outcome, including five (2.5%) who fell, three (1.5%) who became disabled and homebound, 15 (7.6%) who were hospitalized, and three (1.5%) who died. Using binary multivariable logistic regression adjusted for age and gender, we found that patients who were at-risk of frailty and frail at baseline were associated with 5.97(95% CI [1.89- 18.91]; P=0.002) and 6.13 (95% CI [1.86-20.24]; P= 0.003) times higher risk of developing adverse outcomes at 18 months,respectively, than patients who were not frail. The PFFS-M was associated with adverse outcomes.